The poleward naturalization of intracontinental alien plants - Zhang, Zhijie; Yang, Qiang; Fristoe, Trevor S; Dawson, Wayne; Essl, Franz; Kreft, Holger; Lenzner, Bernd; Pergl, Jan; Pyšek, Petr; Weigelt, Patrick; Winter, Marten; Fuentes, Nicol; et al. (Science advances, 2023)
Plant introductions outside their native ranges by humans have led to substantial ecological consequences. While we have gained considerable knowledge about intercontinental introductions, the distribution and determinants of intracontinental aliens remain poorly understood. Here, we studied naturalized (i.e., self-sustaining) intracontinental aliens using native and alien floras of 243 mainland regions in North America, South America, Europe, and Australia. We revealed that 4510 plant species had intracontinental origins, accounting for 3.9% of all plant species and 56.7% of all naturalized species in these continents. In North America and Europe, the numbers of intracontinental aliens peaked at mid-latitudes, while the proportion peaked at high latitudes in Europe. Notably, we found predominant poleward naturalization, primarily due to larger native species pools in low-latitudes. Geographic and climatic distances constrained the naturalization of intracontinental aliens in Australia, Europe, and North America, but not in South America. These findings suggest that poleward naturalizations will accelerate, as high latitudes become suitable for more plant species due to climate change.
Keywords: Plants; Citizenship; klimatické změny; Severní Amerika; rostliny; Humans; North America; státní občanství; Climate Change; lidé; Europe; Evropa; ekosystém; Ecosystem